Candida albicans Osteochondromyelitis after Gastroesophageal Surgery: Two Case Reports - Abdulwares Meiwandi; Hubert Zirngibl; Ahmet Bozkurt (Indian Journal of Plastic Surgery)
Candida osteochondromyelitis is a rare complication after thoracoabdominal surgery. We herein report two such cases after uncomplicated thoracoabdominal surgery, who presented with chronic postsurgical site infection and fistula. CT scans showed fistulas reaching the costochondral areas of the fifth rib. Inflammatory parameters were not elevated. Both patients were treated successfully after the initiation of systemic antimycotic treatment and surgical debridement. We conclude that C. albicans infections should always be considered in cases of chronic postoperative surgical site infections after thoracoabdominal surgery. Additional risk factors do not need to be present. Appropriate therapy consists of the application of systemic antimycotics and surgical debridement.